The neuroprotective effect of ascorbic acid against imidacloprid-induced neurotoxicity and the role of HO-1 in mice - Mudgal, Rajat; Sharma, Satyam; Singh, Sanjiv; Ravichandiran, V. (Frontiers in Neurology, 2023)
Imidacloprid (IMI) is a neurotoxic agricultural pesticide as well as a possible food contamination. Our aim is to explore the relationship between recurrent IMI administration and neuronal toxicity in mice, as well as the potential neuroprotective effect of ascorbic acid (AA), a substance with significant free radical scavenger and having property to block the inflammatory pathways. Mice were categorized as: naïve control (administered drug vehicles for 28 days); IMI-treatment animal group (administered P.O. 45 mg per kg body weight of IMI per day for 28 days and IMI + AA treatment animal group (administered the same IMI dose + 200 mg/kg and AA 200 mg/kg) of AA orally for 28 days. On the 28th day, memory losses were assessed using the Y-maze and novel target identification behavioral tests. Mice were sacrificed 24 hours after the final IMI treatment, as well as hippocampus tissues were utilized to determine oxidative stress biomarkers and HO-1 and Nrf2 gene expression level. The findings demonstrated that IMI-treated mice had substantial impairment of spatial and non-spatial memory functions, as well as reduced antioxidant enzyme and acetylcholinesterase activity. AA neuroprotective action was achieved through the suppression of HO-1 expression as well as the stimulation of Nrf2 expression in hippocampus tissues. In conclusion, recurrent IMI exposure causes oxidative stress and neurotoxicity in mice and administration of AA significantly reduces the IMI toxicity possibly by activation of HO-1/Nrf2 pathway.